THE NOTIONL “POLYCULTURAL” AND “MULTICULTURAL” IN SCIENTIFIC DISCOURSE - Kovalynska, Inna V. (Educological discourse, 2016)
The article deals with thr history of the terms”polycultural” and “multicultural”. It also gives a review of the views of modern scientists as for policultural education in foreign countires is concerned, namely the issue of the mentined above terms usage with the aim of revealing the semantic field of each of the terms and drawng the sphere of each of the terms’ usage, possible overlapping or ex-changing the terms in certain contexts. The article provides review of both American, European, and Russin scholars on the problem and states the difference between the terms “polycultural” and “multicultural”. The author points out the possibility of the terms usage in Ukrainian scientific discourse and she also states differences and similarities of the terms usage in American and European scientific discourse. The author proposes the usage of only one term in Ukrainian scientific discourse.